(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The trade union movement in the Republic of Kazakhstan has entered the stage of qualitative modernization. The necessity to reform the trade union movement in Kazakhstan is due to the inability of trade unions to realize full potential in realms of existing realities, while being on the stage of social modernization, Kazakhstan is in need of strong unions. The article defines the meaning of unions to society and the state through investigation of their essence, protective and representative functions as the main role in formation of civil society and its interaction with the state. Objective and subjective factors of trade unions’ low efficiency are being also identified as a consequence of its authority reduction in society. The necessity to enhance the role of trade unions in the social modernization of the Republic of Kazakhstan requires a new model of social-labor relations based on social partnership, increasing the responsibility of trade unions and employers’ compliance with labor laws of Kazakhstan Republic. Key words: trade unions, the protective function of trade unions, trade union representative function, the historical mission of trade unions, civil society and trade unions, trade unions and the state, labor disputes, social modernization, social stability.